Evaluation of wound healing efficiency using collagen matrices on a thermal burn model - Gafurov Behzod Tohirovich (Zien Journals, 2024)
Every year dozens of new local wound treatment agents are developed and improved in the world, which undergo preliminary testing on laboratory animals due to the presence of common phases of the wound healing process with humans. Wound healing effect was studied on a thermal burn model on Wistar rats in 4 groups: 1st - control (natural wound healing); 2nd - intact animals (normal, without burn). 3rd - experimental ( collagen treatment ); 4th - experimental 2 , comparison group (" Levomekol "); Wound healing was assessed based on the results of planimetry on the 1st, 3rd, 5th, 7th, 9th and 13th days and histological analysis of skin tissue on the 6th, 13th and 20th days. Results. Thermal skin damage resulted in a IIIA degree burn, accompanied by the development of dry coagulation necrosis. The use of collagen matrices restored the total leukocyte count and reduced the area of the burn wound. Histomorphometric studies confirmed the dynamics of skin tissue recovery after the burn. The effectiveness of the matrices was comparable to the pharmacopoeial drug " Levomekol ". A higher wound-healing effect was noted with the use of collagen. Conclusion. The wound-healing effect of collagen matrices was established on the thermal burn model, as evidenced by the results of restoration of the number of leukocytes, reduction of the burn wound area and restoration of the skin histostructure .
Keywords: collagen matrices; thermal burn; skin